Peran Alternative Job Opportunity dalam Memoderasi Pengaruh Work Engagement dan Job Satisfaction terhadap Turnover Intention di Industri Perhotelan - Abrian, Youmil; Lisna, Yuke Permata; Andres, Fran Serano; Afni, Fauza (Departemen Pariwisata Universitas Negeri Padang, 2025)
This study is motivated by the discovery of several facts about the problem of high turnover rates, in the hotel industry in West Sumatra, and there are a lot of employee movement from one hotel to another. The purpose of this study was to determine the role of Alternative Job Opportunity moderating the effect of Work engagement and Job satisfaction on Turnover Intention in the hospitality industry in West Sumatra Indonesia. This research is a quantitative type of causal associative approach with a survey method. The population of this study is staff who have worked for more than 1 year in the hospitality industry in West Sumatra. The sample technique used is purposive sampling. Collecting data for this study by distributing questionnaires that have been tested for validity and reliability. Data analysis using moderation regression with smart PLS 3.0 software. research results (1) There is a negative and significant influence between work engagement variables and turnover intention. (2) A negative and significant effect of job satisfaction on turnover intention was found (3) Simultaneously, a significant effect was found between the variables of work engagement and job satisfaction on turnover intention (4) Alternative Job Opportunity is able to moderate the effect of work engagement and job satisfaction on turnover intention significantly.